Socio-environmental responsibility: the case of a cosmetics industry in the interior of Minas Gerais, Brazil (Research, Society and Development, 2020)
In recent decades, issues related to Social and Environmental Responsibility and sustainable growth in organizations have been constantly debated by society. This study aimed to identify the main social and environmental projects in a cosmetics industry, as well as to understand the perception of local residents and beneficiaries regarding the actions developed by the company. The relevance of the research lies in the fact that social and environmental responsibility is a matter of interest to various publics involved with organizations, whether employees, customers, suppliers, managers or local society. To carry out the study were conducted bibliographic searches in books and articles on the subject, as well as a case study in a cosmetics industry in the interior of Minas Gerais, with interviews with the manager of the company and the application of a questionnaire with residents of the city where the cosmetics industry is located. Through these researches it was possible to understand that the preservation of the institution's profit is directly related to the sustainability investments presented by the company. In addition, it was possible to understand the perception of the local community regarding the social and environmental projects implemented by the organization.